ANALYSIS OF MARKETING FUNCTIONS IN THE PALM OIL VALUE CHAIN: A LITERATURE REVIEW ON THE ROLE OF PURCHASING, SALES, TRANSPORTATION, STORAGE, FINANCING, RISK INSURANCE, QUALITY STANDARDISATION AND CLASSIFICATION, AND MARKET INFORMATION IN MAINTAINING PRODUCT QUALITY AND VALUE - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Palm oil is a strategic commodity that is greatly influenced by the efficiency and integration of marketing functions throughout the value chain. This article examines the role of eight marketing functions—purchasing, sales, transportation, storage, financing, risk insurance, quality standardisation and classification, and market information—in maintaining quality and increasing the value of palm oil products through a systematic literature review. The results of the analysis show that each marketing function has a specific contribution, ranging from determining the quality of initial raw materials, maintaining the physical and chemical integrity of products during distribution, to strengthening differentiation and premium pricing through sustainable standards and certification. The integration of these functions has been proven to increase value chain efficiency, shorten marketing channels, and improve the distribution of added value for farmers and other actors along the chain.